Coping with occupational stress in social environment - Dela Cruz, Jovita S. (Asia Life Sciences : the Asian International Journal of Life Sciences, 2008)
As beings endowed with the capacity to reason, analyze and make rational decisions, man must efficiently oversee the environment for mutual preservation. The overall health of man is crucial to the success of this task. However, stress is a constant factor that disrupts the equilibrium of man's health. This study focuses on the quality of social support and the kind of stress that man experiences at his workplace. The stress vulnerability levels of the chosen samples were measured using the Stress Vulnerability Questionnaire. Furthermore, this study utilized the Social Support Questionnaire to determine the level of social support of the same samples. The scores of these two tests were correlated using necessary statistical tools. The study proves that there is a low stress level for those who have ample social support. The relationship within a social environment is revealed to be a key factor in the reduction of stress thus, granting man the optimal health he needs to fulfill his role as overseer of his immediate surroundings.